THE IMPACTS OF FREE MOVEMENT OF SKILLED LABOUR IN ASEAN UPON VIETNAM: Received: 28th June 2021; Revised: 17th November 2021, 10th January 2022; Accepted: 11th January 2022 - Thuy, Hang Tran; Thi, Ngoc Lan Bui (PEOPLE: International Journal of Social Sciences, 2022)
In the context of the 4.0 technology revolution creating an economic platform transformed from a model based on low-cost labor to a knowledge economy requiring highly skilled workers, Vietnam has witnessed the sharply increasing demand for skilled workers. Since joining ASEAN, Vietnam has proactively participated and implemented free movement of labor commitments within the ASEAN Economic Community. This paper aims to clarify the impact of these commitments on the Vietnamese policies and laws on attracting skilled labor from other ASEAN member states. The paper analyzes both positive and limited aspects of these impacts before 2003 and since 2003 until now. The results of this study show that Vietnam’s commitments to the free movement of labor in ASEAN positively impact the completion of Vietnam policy and regulations on attracting ASEAN skilled labor, but the level of impacts is limited.